KESULITAN MAHASISWA PRODI PAI SEMESTER 4 DALAM MENGHAFAL AL-QUR’AN DI IAIN CURUP - Cikdin; Pepti Zalianti; Ragil Safitri; Reka Widiastuti; Rani selviani (JURNAL ILMIAH RESEARCH STUDENT, 2023)
This research was motivated by the difficulties of IAIN Curup's 4th semester Islamic religious education study program students in memorizing the Koran due to several different factors. This research aims to find out what difficulties students have in memorizing the Koran and what efforts are made to overcome these difficulties. This type of research is qualitative with a descriptive approach. Data type: observation and interviews and data sources are students and teachers. The stages of data analysis techniques are: data reduction, data presentation, and drawing conclusions. Stages of data wetness: source triangulation and data triangulation. The results of the research show that (1) The difficulty of IAIN Curup's 4th semester Islamic religious education study program students in memorizing the Qur'an comes from two factors, namely internal factors and external factors. The internal factors are students' lazy attitude, errors in memorizing methods, and still not reading the Koran fluently. Meanwhile, the external factors are the bad influence of cellphones and the students' different backgrounds. (2) Efforts to overcome the difficulties of memorizing the Qur'an from students themselves are by regularly reciting the Koran, murajaah and managing time and motivating themselves to be better at memorizing. Meanwhile, the teacher's efforts are made by providing value that is equivalent to the student's effort in memorizing and always motivating students that memorizing is not only for achieving grades in lectures but also for getting rewards from Allah SWT.